The relationship in early childhood body composition and physical activity levels regarding fundamental motor skill development - Katherine E. Spring; Alexandra V. Carroll; Danielle D. Wadsworth (BMC, 2023)
Abstract Background Fundamental motor skills (FMS) are considered essential for sport participation and might be deficit in obese children. While evidence indicates that physical activity (PA) levels impact motor skill development, the relationship between body composition, PA, and motor competence, particularly in early childhood, is not thoroughly understood. We aimed to determine if PA, fat mass (FM), and fat-free mass (FFM) are predictors of FMS. Methods Preschoolers (n = 47) from two preschools were assessed for FMS, PA, and body composition. Peabody Developmental Motor Scales (PDMS-2) subscale scores were used to assess FMS. PA was assessed with a wrist-worn accelerometer for five days during school. FM and FFM were measured with foot-to-foot bioelectrical impedance. Results Linear regressions indicate significant models for stationary skills (SS) (F = 4.57, p = .004) and object manipulation skills (OMS) (F = 4.66, p = .003). FFM was the only significant predictor of SS (t = 3.98, p < .001) and OMS (t = 3.50, p = .001). FM and all intensities of PA were nonsignificant predictors in all models. Conclusions These results indicate that interventions that target improving or maintaining FFM may improve FMS.